(untitled) (World Economics and Finance Bulletin, 2024)
Concepts are developed. Business stability ensuring mechanism of enterprise model in modern economy digitalization conditions is grounded based on complex casual-consequential chains of business management metrics system of the enterprise with its marketing complex. Each component of the business management metrics system of the modern enterprise is proved to form particular components of the general model for business stability ensuring mechanism.